2015
DOI: 10.1080/09712119.2015.1102727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional traits on subsequent reproduction performance of Murrah buffaloes in India

Abstract: A study was conducted on calving records of Murrah buffaloes to study the influence of various functional traits on subsequent reproductive performance. The effects of calving abnormalities, uterine health problems, female fertility problems and udder health problem on calving to first service (CFS), service period (SP), dry period (DP) and calving interval (CI) were studied by the leastsquares method using the SAS package. The increase in CFS, SP, DP and CI was 27.07%, 18.71%, 96.74% and 6.70%, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This study found that retained fetal membrane regarded as the main factor which affects the reproductive performance within other uterine disorders. This study agreed with the previous studies Manoja et al (9) they reported that retained placenta had significant impact on reproductive performance of Murrah buffaloes. The obvious higher productive losses associated with retained placenta could be a considerable risk cause for toxic puerperal metritis in Iraqi cow-buffaloes (15).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found that retained fetal membrane regarded as the main factor which affects the reproductive performance within other uterine disorders. This study agreed with the previous studies Manoja et al (9) they reported that retained placenta had significant impact on reproductive performance of Murrah buffaloes. The obvious higher productive losses associated with retained placenta could be a considerable risk cause for toxic puerperal metritis in Iraqi cow-buffaloes (15).…”
Section: Discussionsupporting
confidence: 94%
“…Resulting increased veterinary costs because of lower reproduction, culling rates associated with decrease milk production and longevity of cow-buffaloes. As the rate of postpartum disorders increased the incidence of ovarian dysfunction was increased following the postpartum disorders in buffaloes (9). Several studies have considered the influence of uterine complications during postpartum period on reproductive performance in high yielding dairy cows (10).…”
Section: Introductionmentioning
confidence: 99%
“…Buffalo is an important dairy animal having unique qualities like efficient converter of low‐grade coarse feedstuff, ability to withstand adverse weather conditions, and resistance to many diseases of cattle (Manoj et al, ). Buffaloes are the second largest source of milk supply in the world and play an important role in the rural economy through their contribution to food, draught power and employment generation (Nanda & Nakao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such selection on production traits though has increased milk yield in dairy animals, but it has also lead to an increased incidence of disease and reproductive problems. Fertility, udder and uterine problems are some of the important functional indicator traits, which are associated with higher culling rates, reduction in longevity of dairy animals, increased veterinary costs, losses due to lower production and discarded milk (Manoj et al 2015). Various countries have incorporated functional traits, viz.…”
mentioning
confidence: 99%